Integrating Local Wisdom and Sustainable Development Goals: Contextual Learning Through Klepon Village in Indonesian Primary Education - Sari, Yunita; Hendratno, Hendratno; Gunansyah, Ganes; Mariana, Neni; Suprapto , Nadi (Journal of Innovation and Research in Primary Education, 2025)
This study aims to explore the integration of local cultural practices and Sustainable Development Goals (SDGs) into contextual learning through the case of Klepon Village in Bulang, Sidoarjo, Indonesia. Klepon, a traditional Indonesian snack, is not only a culinary heritage but also a potential educational tool for primary school students. The main research questions of this study are: (1) How can local cultural practices, particularly the production of Klepon, be integrated into the primary school curriculum? (2) What impacts does this integration have on students’ literacy, numeracy, socio-cultural awareness, and character development? Using a qualitative descriptive approach with case study methods, the research involved 25 primary school students and 3 teachers over a period of three months to examine how Kampung Klepon serves as a contextual learning resource in various subjects, including language, mathematics, and science-social studies (IPAS). The findings reveal that integrating the cultural practice of klepon production enhances students’ literacy, numeracy, and socio-cultural awareness. It also fosters students’ character development, entrepreneurial mindset, and environmental consciousness aligned with SDGs. Specifically, students showed improvements in storytelling ability, basic arithmetic skills related to measuring ingredients, and environmental awareness through waste management practices. The study demonstrates that such a local-based approach supports the implementation of Indonesia’s Merdeka Curriculum and promotes transformative education rooted in ethnopedagogy. This research contributes to the discourse on contextual and sustainable education by offering an innovative model that links traditional knowledge, school curriculum, and global educational goals. It also highlights the importance of community-school collaboration in creating meaningful learning experiences.